Cómo ser un mejor oyente (Assemble You, 2022)
Welcome to Audio Learning by Assemble You. How many times have you had a conversation that just ... doesn't feel right? You are being heard, but not listened to. If you're honest with yourself, how many times have you been the one not listening properly? Poor listening results in mistakes and misunderstandings, which, in turn, can lead to ineffective decisions and costly business mistakes. By not listening, you miss out on potentially great suggestions from people you might as well have hired. And, on a personal level, not listening properly leads to resentment and a loss of team cohesion. In this recording, we'll give you some practical techniques to transform your listening skills. Learning Objectives Learn about the drawbacks of poor listening, and the inefficiency with which the average human listens Learn tricks to improve your listening skills significantly above the average person.